If I stay a novel - Forman, Gayle (New York Dutton Books, 2009)
While in a coma following an automobile accident that killed her parents and younger brother, seventeen-year-old Mia, a gifted cellist, weighs whether to live with her grief or join her family in death
Sequel: Where she went
1
Keywords: Cello -- Fiction; Coma -- Fiction; Death -- Fiction; Family life -- Oregon -- Fiction; Medical care -- Fiction; Musicians -- Fiction; Oregon -- Fiction